Epidemiological studies on the health impact of air pollution in Japan: their contribution to the improvement of ambient air quality - Masayuki Shima (Environmental Health and Preventive Medicine)
In Japan, during the high economic growth period (1950–1960s), air pollution due to sulfur dioxide (SO2) and dust derived from large-scale factories and power plants was apparent in many industrial districts, and it caused serious health problems such as the so-called “Yokkaichi Asthma.” Many epidemiological studies have revealed the relationship between air pollution and respiratory diseases, and have provided scientific evidence for the regulatory control of air pollution. The concentration of SO2 has markedly decreased since the 1970s, and its adverse health effects have improved. In contrast, increased automobile traffic has caused considerable traffic-related air pollution, including nitrogen oxides (NOx) and particulate matter (PM). Epidemiological studies in Chiba and Tokyo revealed that the prevalence and incidence of asthma were significantly higher among individuals living in roadside areas than among those living in other areas. Large-scale epidemiological studies conducted in urban districts have revealed an association between traffic-related air pollution and the onset of asthma in schoolchildren and persistence of asthmatic symptoms in preschool children. Thereafter, the concentrations of NOx and PM gradually decreased due to the control measures based on the Automobile NOx/PM Law enforced in 2001. Thus, epidemiological studies have contributed to a reduction in air pollution caused by automobile exhaust emissions. Recently, the adverse health effects of ambient fine PM (PM2.5) and ozone (O3) at ground level have become an international concern. Our epidemiological studies showed that short-term exposure to considerably low concentrations of PM2.5 and O3 was associated with a decrease in pulmonary function among asthmatic children and increased airway inflammation in healthy adolescents. The effects of exposure to PM2.5 during pregnancy and early childhood on children’s development have also been reported. These air pollutants consist of not only emissions from primary sources but also secondary formations in the atmosphere. They are affected by climate change and spread worldwide. Air quality control measures and climate change adaptation and mitigation strategies are synergistic, and will have co-benefits on human health. Therefore, global efforts are required to protect populations from the health risks posed by these air pollutants.